2023
DOI: 10.1177/07356331221137253
|View full text |Cite
|
Sign up to set email alerts
|

AI and Recognition Technologies to Facilitate English as Foreign Language Writing for Supporting Personalization and Contextualization in Authentic Contexts

Abstract: English as Foreign Language (EFL) writing is challenging for students due to the lack of related lexical resources to inspire them for meaningful writing besides grammar feedback. Moreover, it is crucial to design personalized feedback based on students’ original writings in helping to improve their writing abilities. Therefore, we developed Smart RoamLingo app to help writing meaningful content in authentic contexts with sample sentences based on texts generated by recognition technologies named as AI-Sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…The qualitative findings of the current study further corroborated these quantitative findings, as learners exhibited positive responses toward the integration of the AI-assisted language learning approach into their writing activities. Consistent with the findings of Hwang et al (2023), the present study suggests that the positive outcomes can be attributed to the personalized language learning experience facilitated by the AI-assisted language learning tool during collaborative writing tasks. By using the AI-powered tool, learners had the opportunity to work at their own pace and receive immediate feedback, enabling them to produce better-written texts.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The qualitative findings of the current study further corroborated these quantitative findings, as learners exhibited positive responses toward the integration of the AI-assisted language learning approach into their writing activities. Consistent with the findings of Hwang et al (2023), the present study suggests that the positive outcomes can be attributed to the personalized language learning experience facilitated by the AI-assisted language learning tool during collaborative writing tasks. By using the AI-powered tool, learners had the opportunity to work at their own pace and receive immediate feedback, enabling them to produce better-written texts.…”
Section: Discussionsupporting
confidence: 89%
“…The intelligent tutoring system's feedback, provided within an AI-assisted language learning environment, had a significant impact on the development of students' academic writing skills. Hwang et al (2023) conducted an experimental study with a control group to explore the effects of an AI-based writing feedback tool on undergraduate EFL students' writing performance. The results demonstrated that the experimental group, utilizing the AI-assisted tool, outperformed the control group in writing tasks.…”
Section: Artificial Intelligencementioning
confidence: 99%
“…Computer's advanced cognitive abilities can now be self-taught without direct human intervention or any reprogramming processes. The application of this type of AIs in education has been extensively studied in the area of writing communication (Hwang et al. , 2023; McKnight, 2021; Wette, 2017),…”
Section: Findings and Discussionmentioning
confidence: 99%
“…With its natural language processing capabilities, AI can comprehend and analyze learners' linguistic output, offering tailored feedback that aids them on their personalized journey towards language mastery. This innovative approach fosters a more individualized and practical language learning experience (Hwang et al, 2023). Moreover, implementing AI technologies is crucial in promoting social interaction and advancing language skills.…”
Section: Literature Reviewmentioning
confidence: 99%